Facile processing of ?-alumina for potential energy storage - Misran H.; Zini F.A.M.; Salim M.A.; Ramesh S. (2023)
Mesoporous ?-alumina with relatively high surface area of ca. 590 m2/g and pore size of ca. 2.0 nm to ca. 9.7 nm were successfully processed using facile and cost-effective method in the presence of renewable, low-cost templates. Controlled addition of water during the processing of the materials was found to control the rapid hydrolysis rate of alumina precursors resulting in mesoporous formation. In addition, these materials porosity was made up from framework porosity as well as textural porosity given rise from the aggregations of ?-alumina nanoparticulates. Regardless of the materials specific surface area value, the competitive adsorption amount of energy gas in 68 % humidity environment increased as relative crystallinity of the materials increased. (2012) Trans Tech Publications, Switzerland.